Gender and academic discipline influences on EFL learners' perceptions of video-based instruction - Olusiji Lasekan; Margot Teresa Godoy Pena (Australian Journal of Applied Linguistics)
This study explores the perceptions of educational videos in English as a Foreign Language (EFL) learning among students from different gender groups and academic disciplines, specifically Social Sciences, Humanities, STEM, and Health Sciences. Using an experimental survey-based design, the research examines how male and female learners, as well as students from various academic fields, perceive video-based instruction across five key dimensions: cognitive processing, affective response, contextual learning, perceived relevance, and usefulness. Cognitive Load Theory (CLT) is applied to provide a framework for optimizing video-based EFL instruction by managing cognitive load and enhancing learner engagement across diverse groups. The findings indicate that females tend to rate videos higher in Affective Response and Perceived Usefulness, while men show lower ratings in Perceived Relevance and Cognitive Processing, with consistent scores overall. Faculty-based differences were also evident: Social Sciences and Humanities students rated videos higher in terms of affective response, contextual learning, and perceived relevance. These results highlight the importance of tailoring video content to meet the diverse needs of learners based on gender and academic discipline. The study suggests that educators should integrate both interactive and structured materials to enhance learning outcomes for all students.